High Flow Bypass and Trapping of the Fusiform Aneurysm of Right Middle Cerebral Artery Using Y Graft: A Noble Surrogate - Shrestha, Bishal; Gurung, Pritam; Badinski, Tina; Malla, Samridha; Acharya, Samir; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Fusiform aneurysms of the middle cerebral artery (MCA) are a very demanding vascular pathology for the neurosurgeons rendering to its complexity and perplexing to execute adequate clipping. On that account, trapping is a virtuous alternative for these lesions accompanied by vascular reconstruction.A 21-year-old gentleman presented with the chief complaints of headache and weakness of left side of upper and lower extremities with facial deviation toward left side and slurring of the speech since 4 months. Cerebral CT angiography showed fusiform dilatation involving the vessel in the right M1 segment of the MCA. After construction of high flow bypass (ECA-MCA) on superior and inferior trunk of the MCA using long saphenous vein graft in the form of Y shaped design, fusiform aneurysm was trapped. He was discharged on 12th post-operative day with mRS 1. High flow bypass and trapping is one of alternatives for the treatment of large fusiform shaped aneurysm in the MCA.